Sistem Informasi Akademik Berbasis Web untuk Mendukung Pembelajaran Jarak Jauh di SD Anak Bangsa - Jovan Jeremi; Lily Puspa Dewi; Krisna Wahyudi (Jurnal Infra, 2021)
Anak Bangsa Elementary School is a private school located in Surabaya. Schools have many academic administrative processes, such as personnel data collection, assessment, attendance, finance and report cards. At this time, Anak Bangsa doesn’t have a system or database. All administrative processes, data storage and processing are done manually, so errors often occur. In 2019, the Covid-19 outbreak emerged in Indonesia, which caused face-to-face learning process to switch to distance learning. It is undeniable that Anak Bangsa must also change its learning methods and adapt to this situation.Answering these problems, Anak Bangsa School must have an information system to process data that supports distance learning. The system is made based on a website using PHP and Javascript programming languages and mysql database. The features of this system include calculating grades, attendance, finance, online tests, and generating report cards.From the results of the questionnaire, the level of satisfaction with the overall program is 74% good and 26% very good. It can be concluded that this program is able to meet the needs of Anak Bangsa in managing academic data and supporting distance learning process.